Maqashid Syariah: Perbandingan Antara Pemikiran Al - Ghazali dan Najmuddin At - Thufi - Muhammad Habibul Amin; Dhiauddin Tanjung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to compare the two concepts of Maqashid al-Syari'ah from al-Ghazali and at-Thufi with a focus on finding similarities and differences between their views. Maqashid al-Syari'ah refers to the principles or goals that are the basis of Islamic law, which aim to maintain human welfare and justice in society. Social changes arising from developments over time and the dynamics of society encourage scholars to deepen their studies of Maqashid al-Syari'ah seriously to find legal innovations that are needed to deal with existing social changes. The research method applied is qualitative in nature by utilizing library research, which involves the collection, analysis and thorough narrative interpretation of visual data to understand thoroughly and comprehensively the concept of maqashid al-Syari'ah from the perspective of al-Ghazali and at -Thufi. The results and discussion of this article confirm that the main aim of all Islamic religious teachings, including the Qur'an and hadith, is benefit. Al-Ghazali groups benefits into three parts, namely maslahah dharuriyah (urgent interests), hajiyah (necessary interests), and tahsiniyah (interests that improve the quality of life). On the other hand, At-Thufi does not divide benefits into these categories; for him, benefit is benefit, without needing to be shared. However, both agree that the essence of this benefit concept is to protect human welfare itself.